Volume 4: Turbo Expo 2004 2004
DOI: 10.1115/gt2004-53829
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Unsteady Flow Field in an Axial Gas Turbine Rim Seal Configuration

Abstract: The fluid flow in gas turbine rim seals and the sealing effectiveness are influenced by the interaction of the rotor and the stator disk and by the external flow in the hot gas annulus. The resulting flow structure is fully 3-dimensional and time-dependant. The requirements to a sufficiently accurate numerical prediction for front and back cavity flows are discussed in this paper. The results of different numerical approaches are presented for an axial seal configuration. This covers a full simulation of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 0 publications
3
55
1
Order By: Relevance
“…[33], Savov et al [34], Schädler et al [35], Jakoby et al [24] and Town et.al. [36] have all indicated unsteady rim seal cavity flow features which are unrelated to blade passing.…”
Section: Experimental Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…[33], Savov et al [34], Schädler et al [35], Jakoby et al [24] and Town et.al. [36] have all indicated unsteady rim seal cavity flow features which are unrelated to blade passing.…”
Section: Experimental Evidencementioning
confidence: 99%
“…For "short seals", such as those in figure 3, the surface areas in the seal may be sufficiently small for the surface drag on the rotor and stator to be negligible in the seal flow. Counter to this argument is the observation in, for example, references [11,24] that rotating cavity, seal and annulus flows may be subject to 3D rotating flow modes that significantly affect ingestion. For more extended seals involving overlapping rotor and stator parts the rotation and surface drag may also affect the flow in the seals as, for example, suggested by Graber et al and supported by computations for a chute rim seal in reference [25].…”
Section: Multi-mode Ingestionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case the throughflow Reynolds number C w = 3x10 4 , the rotational Reynolds number Re ∅ = 7.4x10 6 , and the throughflow parameter = 0.09. CFD results for this case were reported and analysed in detail in reference [10].…”
Section: Baseline Flow and Heat Transfermentioning
confidence: 99%
“…For example, Cao et al [5] and Jakoby et al [6] have observed large scale flow structures in disc cavities with ingestion. These rotate at a lower speed than the disc.…”
Section: Introductionmentioning
confidence: 99%